(untitled) (Praxis Educativa, 2020)
This article accounts for an exploratory-descriptive research, whose objective is the identification and analysis of different theories of education present in the practices of democratic citizenship at educational institutions of the Province of Córdoba. It is based on the analysis of the representations students, teachers, and administrators make of their practices. It is grounded on the hypothesis that the theories of education configuring the practices of democratic citizenship may be explored and identified, and that these are associated -in part- with the ways of conceiving knowledge, learning, subjects, and the relationship between the educational institution and society. Thus, there is a classification of democratic practices, prepared as a temporary result of the analytical matrix used for the interpretation of the meanings explored in students, teachers, and administrators.